Can magnifying endoscopy with narrow-band imaging discriminate between carcinomas and low grade adenomas in gastric superficial elevated lesions? - Nonaka, Takashi; Inamori, Masahiko; Honda, Yasushi; Kanoshima, Kenji; Inoh, Yumi; Matsuura, Mizue; Uchiyama, Shiori; Sakai, Eiji; Higurashi, Takuma; Ohkubo, Hidenori; Iida, Hiroshi; Endo, Hiroki; Fujita, Koji; Kusakabe, Akihiko; Atsukawa, Kazuhiro; Takahashi, Hisao; Tateishi, Yoko; Maeda, Shin; Ohashi, Kenichi; Nakajima, Atsushi (Endoscopy International Open, 2016)
Background and study aims: The aim of this study was to investigate the capability of magnifying endoscopy with narrow-band imaging (ME-NBI) to discriminate between early carcinomas (EC) and low grade adenomas (LGA) in gastric superficial elevated epithelial neoplasias.Patients and methods: We investigated 100 consecutive cases of gastric superficial elevated epithelial neoplasias that were removed using endoscopic submucosal dissection. The pathological diagnostic criteria were based on the revised Vienna classification; category 4 (mucosal high grade neoplasia) and category 5 (submucosal invasion by carcinoma) lesions were diagnosed as EC, whereas category 3 (mucosal low grade neoplasia) lesions were diagnosed as LGA. The associations between the postoperative pathological diagnoses and the ME-NBI findings were analyzed, and included the shape, specification, and area of irregularity in the microvascular architecture (MV) and the microsurface structure (MS).Results: Seventy-nine EC and 21 LGA cases diagnosed postoperatively were evaluated retrospectively. The lesion size (median; range (mm)) was significantly larger in the EC group (14; 2 – 95) compared to the LGA group (5; 2 – 16) (P < 0.001). Wavy forms in the MV shapes (P = 0.031), extension in the MV specifications (P = 0.035), and area with MV irregularity (P = 0.001) were found to be statistically significant predictive findings for EC. Villous forms in the MS shapes (P = 0.026), enlargement in the MS specifications (P = 0.044), and area with MS irregularity (P = 0.021) were also found to be statistically significant predictive findings for EC. The rates of preoperative sensitivity, specificity, and diagnostic accuracy of ME-NBI for discriminating EC were 86.1 %, 38.9 %, and 75 %, respectively. Conclusions: The present study suggests that ME-NBI is useful for the differential diagnosis of EC and LGA in gastric superficial elevated epithelial neoplasias.Study registration: UMIN000012925.